INCREASING POETRY WRITING SKILLS IN INDONESIAN LESSONS THROUGH VISUAL MEDIA CLASS V SDN TAMBAK KEMERAAN - Umi Khanifah; Agung Setyawan (Citra Dharma Cindekia, 2022)
This study aims to improve the poetry writing skills of Indonesian language subjects in fifth grade students of SDN Tambak Kemeraan by using visual media. This type of research is Classroom Action Research using the Kemmis and MC Taggart models by conducting two cycles during the research. Each cycle is carried out once. The subjects in this study were the fifth grade students of SDN Tambak Kemeraan 2021-2022, totaling 24 students consisting of 11 male students and 13 female students. This study uses several data collection techniques, namely observation, tests, documentation, and others that are guided by the development of the instrument. The data analysis technique in this study used descriptive quantitative data analysis techniques. The results of the Classroom Action Research show that the use of visual media can improve students' poetry writing skills. This is indicated by the increase in the average value of students and the results of student learning completeness.